2022
DOI: 10.19175/recom.v12i0.4617
|View full text |Cite
|
Sign up to set email alerts
|

Parada cardiorrespiratória e cerebral: construção e validação de cenário simulado para enfermagem

Abstract: Objetivo: construir, validar e testar um cenário de simulação clínica para o manejo da parada cardiorrespiratória e cerebral para o ensino de enfermagem.  Método: foi realizado design de estudo metodológico de desenvolvimento educacional realizado em três fases: elaboração de cenário simulado sobre parada cardiorrespiratória cerebral, validação do conteúdo e teste do cenário simulado com estudantes de graduação em enfermagem. A análise dos dados se deu pelo Índice de Validade de Conteúdo, considerando-se adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Corroborating these findings, a study found that most students agreed that the simulation contributed to the development of logical reasoning, the execution of teamwork, nursing techniques and procedures, in addition to assisting in autonomy and professional posture. 14 This improvement after clinical simulation can be identified mainly among younger students, aged between 18 and 28 years, especially with regard to the acquisition of cognitive and practical knowledge, as well as self-confidence. 15…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Corroborating these findings, a study found that most students agreed that the simulation contributed to the development of logical reasoning, the execution of teamwork, nursing techniques and procedures, in addition to assisting in autonomy and professional posture. 14 This improvement after clinical simulation can be identified mainly among younger students, aged between 18 and 28 years, especially with regard to the acquisition of cognitive and practical knowledge, as well as self-confidence. 15…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate of individuals is closely related to the speed with which care is started, as well as to the qualification of professionals involved in care, so that the assistance provided is effective to reverse the patient's clinical condition. 14 It is in this context that the development of clinical skills of nursing students is extremely relevant, since, most of the time, it is this professional, a nurse, who performs the first care, identifies that the patient is on CRA and already starts the cardiopulmonary resuscitation maneuvers. 2 Nurses' clinical competence is crucial for providing accurate care to patients on CRA, and education plays a key role in improving this competence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O Índice de Validade de Conteúdo (IVC) foi considerado satisfatório quando atingiu um resultado igual ou superior a 0,80, de acordo com a seguinte fórmula: n o de respostas 3 ou 4 dividido pelo número total de respostas 9,12 . O teste exato de distribuição binomial, com nível de significância de 5%, foi empregado para a validação de conteúdo, considerando uma proporção de 80% e uma significância estatística de p>0,05, uma vez que a hipótese nula era a de concordância, conforme observado em pesquisas anteriores [13][14][15][16] .…”
Section: Métodounclassified